Profil Mahasiswa Sosiologi Fisip Universitas Riau: Studi Tentang Spekulasi Dramaturgi Bagi Pengguna Instagram - Aisah Aisah; Nurhamlin Nurhamlin (Journal Innovation In Education, 2025)
The development of social media has become one of the most interesting phenomena in the history of modern information technology. From its humble beginnings to a complex global network, social media has changed the way we communicate and interact with one another. While its impact has been very positive in many ways, it is important to continue to consider the social and ethical implications of social media. This study uses a descriptive qualitative research method. The author collected data through interviews, a method where the subject and researcher meet in a specific situation to obtain information. The data sources were obtained from Sociology students at the University of Riau through interviews with purpose sampling. The results of this study have shown that life on social media, as depicted in the dramaturgical speculation on both the front stage and backstage by Instagram users, is indeed real. Instagram users tend to present a different side of themselves on the front stage, and similarly, in the backstage of real life—which is unknown to many people—individuals tend to behave according to their true personalities without any external pressure, and they tend to be themselves.